2016
DOI: 10.1007/s11629-015-3744-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon contents, aggregate stability, and humic acid composition in different alpine grasslands in Qinghai-Tibet Plateau

Abstract: Alpine grassland soils on Qinghai-Tibet Plateau store approximately 33.5 Pg of organic carbon (C) at 0-0.75 m depth and play an important role in the global carbon cycle. We investigated soil organic C (SOC), water-soluble organic C (WSOC), easily oxidizable organic C (EOC), humic C fractions, aggregate-associated C, aggregate stability, and humic acid (HA) composition along an east-west transect across Qinghai-Tibet Plateau, and explored their spatial patterns and controlling factors. The contents of SOC, WSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…However, for different grassland types, the different methods differed significantly, with a larger value in the meadow than steppe grassland. The results of this experiment were similar to those of previous studies [13, 46, 47]. Ding et al (2017) concluded that the alpine meadow’ mean SOCD was higher than that of the alpine steppe in 2000 (2.71 and 6.96 kg cm -2 , respectively) and 2010 (2.95 and 7.37 kg cm -2 , respectively) [47].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, for different grassland types, the different methods differed significantly, with a larger value in the meadow than steppe grassland. The results of this experiment were similar to those of previous studies [13, 46, 47]. Ding et al (2017) concluded that the alpine meadow’ mean SOCD was higher than that of the alpine steppe in 2000 (2.71 and 6.96 kg cm -2 , respectively) and 2010 (2.95 and 7.37 kg cm -2 , respectively) [47].…”
Section: Discussionsupporting
confidence: 89%
“…Ding et al (2017) concluded that the alpine meadow’ mean SOCD was higher than that of the alpine steppe in 2000 (2.71 and 6.96 kg cm -2 , respectively) and 2010 (2.95 and 7.37 kg cm -2 , respectively) [47]. The soil carbon content of different grassland types on the QTP had obvious zonal differences that were consistent with the distribution of soil and grassland types [46]. The reason for this may be that higher precipitation and lower temperatures influence meadow grassland to a greater extent than steppe grassland, and the decomposition process of SOM is restricted, which results in higher accumulation of SOC.…”
Section: Discussionmentioning
confidence: 99%
“…(Gao et al 2007;Wang et al 2002). Alpine grasslands, covering approximately 35% of the Qinghai-Tibet Plateau area, are the major pastureland of the region (Zheng et al 2000), and approximately 33.5 Pg of organic C is stocked in the 0-75 cm layer of soil (Cao et al 2016). Therefore, many studies have estimated the SOM stocks in this region, indicating a considerable accumulation of SOM (Tan et al 2010;Yang et al 2008;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SOM is heterogeneous and consists of various fractions with different stability, resolution, and rotation rates. Two dominant fractions of SOM are the labile soil organic C (SOC) fractions and the chemically recalcitrant SOC fractions, which are potential indicators of global climate change (Steinberg 2003;Cao et al 2016;Hu et al 2017;Wang et al 2016). The latter (e.g., humic substances) is traditionally separated into humic acid (HA), fulvic acid (FA), and humins (HN) based on the solubility characteristics of each fraction, and the humus composition is an essential characteristic of humic substances in SOM.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Permafrost distribution and other features are closely related to vegetation types, and their changes can potentially affect SOC dynamics. 16,31,35,36 Some previous studies have provided valuable information on the SOC pools and fraction dynamics under different vegetation types on the QTP (e.g., 16,25,27,[36][37][38] ). For example, Wu et al 16 suggested that the permafrost and land cover types were the main controlling factors for the LFOC content and stock, and that permafrost degradation would inevitably lead to a decrease in the LFOC, thus accelerating the decomposition of SOC.…”
Section: Introductionmentioning
confidence: 99%